2019
DOI: 10.1536/ihj.18-647
|View full text |Cite
|
Sign up to set email alerts
|

Case of Incomplete Kawasaki Disease with No Symptoms Except Fever Causing the Development of Coronary Aneurysm

Abstract: Incomplete Kawasaki disease (iKD), which does not satisfy the standard KD diagnostic criteria because the required number of principal symptoms is not met, sometimes causes coronary aneurysms. Here we report the case of a patient with iKD who presented with only one principal symptom that resulted in the development of coronary aneurysm, as evidenced by angiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…However, nationwide surveys have shown that the incidence of CAA development in Japan has not changed substantially in recent years (2013-2014: CAAs, 2.6%; and giant aneurysms, 0.20%; 2015-2016: CAAs, 2.3%; and giant aneurysms, 0.13%; and 2017-2018: CAAs, 2.6%; and giant aneurysms, 0.11%). Additionally, in clinical practice, some patients with CAAs show resolution of fever with initial IVIG therapy or naturally without treatment . Thus, even if effective treatments for immunoglobulin-refractory KD are established, the development of KD-related CAAs cannot always be prevented.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…However, nationwide surveys have shown that the incidence of CAA development in Japan has not changed substantially in recent years (2013-2014: CAAs, 2.6%; and giant aneurysms, 0.20%; 2015-2016: CAAs, 2.3%; and giant aneurysms, 0.13%; and 2017-2018: CAAs, 2.6%; and giant aneurysms, 0.11%). Additionally, in clinical practice, some patients with CAAs show resolution of fever with initial IVIG therapy or naturally without treatment . Thus, even if effective treatments for immunoglobulin-refractory KD are established, the development of KD-related CAAs cannot always be prevented.…”
Section: Introductionsupporting
confidence: 76%
“…Additionally, in clinical practice, some patients with CAAs show resolution of fever with initial IVIG therapy or naturally without treatment. 16 , 17 , 18 , 19 , 20 , 21 Thus, even if effective treatments for immunoglobulin-refractory KD are established, the development of KD-related CAAs cannot always be prevented.…”
Section: Introductionmentioning
confidence: 99%